AB0115 BFGF increases HES1 and HEY1 expressions in murine chondrocytes in vitro. (23rd January 2014) - Frazier-Mironer, A.; Tahiri, K.; Hassaine, N.Z.; Corvol, M.; Rannou, F.; Savouret, J.-F.; Richette, P.
Abstract : Background: During osteoarthritis (OA), articular chondrocytes undergo cellular changes, such as proliferation and dedifferenciation, reminiscent of growth plate (GP) terminal différentiation. Among the factors and the signaling molecules which control this process during development, some of them may be involved in the pathogenesis of adult cartilage degradation. basic FGF (bFGF) is a well-known mitogenic factor and it is found at increased concentrations in synovial fluid from OA patients. In chondrocytes in vitro, bFGF induces a dedifferentiation, characterized by a decrease of Collagen type II expression. Recently, it has become evident that the Notch signaling family contributes to chondrogenesis. After activation by extracellular proteolytic cleavages, the intracellular fragment of Notch receptor activates Hes and Hey transcriptional factors. Notch1 has been proposed to be involved in OA degradative process but the role played by Hes/Hey in chondrocytes remains elusive. Objectives: The purpose of this study was to investigate the effects of bFGF on the Notch/Hes/Hey pathway in chondrocytes in vitro . Methods: Murine chondrocytes were established in primary culture and treated or not with bFGF (1-10 ng/mL) for different periods of time. Notch1, Hes1 and Hey1 expressions were analyzed by qRT-PCR and western blot. Target genes were determined by using specific siRNA. Results: Notch1 mRNA expression was not modified in the first 3 hours of bFGF exposure, and increased progressively thereafter, with a 5-fold stimulation after 8 hours of exposure. Hes1 mRNA expression was stimulated in a rapid and robust way by bFGF (8-fold higher than in controls after 80 mn exposure). This stimulation was followed by a progressive decrease, although Hes1 expression stayed more elevated than in controls until 24h. Hes1 protein expression was also stimulated by bFGF. Hey1 mRNA expression was also transiently stimulated by bFGF, with a lower maximum level and slightly later than that found on Hes1 expression (5-fold higher than in controls after 3h exposure). The use of specific inhibitors showed that bFGF-induced stimulation of Hes1 or Hey1 mRNAs were transcriptional, and independent of the canonic Notch/Hes pathway. However, while the stimulating effect of bFGF was direct on Hes1 transcripts, its effect on Hey1 mRNA required de novo protein synthesis. The use of an anti-Hes1 siRNA strongly suggested that bFGF-induced Hey1 stimulation is under the control of Hes1. Moreover, the bFGF-induced decrease of Collagen type II mRNA expression was partially inhibited by the transfection of an anti-Hes1 siRNA, suggesting that Col2 is a Hes1 target gene. Conclusions: Hes1 and Hey1 are novel target genes of bFGF in murine chondrocytes in vitro and do not involve de novo activation of Notch1 signaling pathway. The bFGF-induced stimulation of Hey1 is dependant of Hes1. Moreover, the Hes1/Hey1 pathway may play a role in bFGF-induced dedifferentiation, by influencing the expression of Collagen type II. Disclosure of Interest: None Declared